Health teachers' ethical conflict experiences in the COVID-19 situation: a qualitative content analysis - Kyoung Mi Lim; Sohyune Sok (Frontiers Media S.A., 2024)
BackgroundIn the context of the COVID-19 pandemic, health teachers who are responsible for the health of school staff and students are experiencing many ethical conflicts, and research on this is needed.ObjectiveThis study was to investigate and explore the ethical conflicts experienced by health teachers during the COVID-19 pandemic situation.MethodsThis was a qualitive study using directed content analysis applied to the four principles of biomedical ethics. Study participants were a total of 26 health teachers in Seoul, South Korea. In-depth individual interviews were conducted with 14 health teachers, and focus group interviews were conducted with the other 12 (2 teams with each 6 persons). Data were collected between May-June 2022, and analyzed using a deductive approach among the qualitative content analysis of Elo and Kyngäs. This study satisfied the four aspects of credibility, transferability, dependability, and confirmability presented by Guba and Lincoln (1989) to secure the reliability of qualitative research.ResultsThe ethical conflicts related to the four principles of biomedical ethics advocated by Beauchamp and Childress (autonomy, non-maleficence, beneficence, and justice), and the ethical conflicts in which overlap with the two principles of autonomy and non-maleficence, and the ethical conflicts related to miscellaneous matters or relationships, which were not included in the four principles, were investigated as the main 6 categories of ethical conflicts experienced by health teachers. Based on this, 10 generic categories and 17 subcategories were derived.ConclusionThis study could be used as primary data for policy development and intervention research. Such engagements can help identify ethical conflicts faced by health teachers in infectious disease crises, thus improving their ability to cope.